2016
DOI: 10.1038/jp.2015.219
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of unplanned extubations in neonates through process standardization

Abstract: UPEs in neonates can be reduced with process standardization and frontline staff education, emphasizing vigilant endotracheal tube (ETT) maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 12 publications
3
34
0
2
Order By: Relevance
“…This increase can be attributed to the hospital's having moved some experienced critical care nurses to support a newly set-up branch hospital, which decreased the quality of care in the ICU of our hospital's main branch ICU. Other studies [5,1618] report similar findings in different populations. Fontanez-Nieves et al [16] reported a significant reduction of UE from 16.1 to 4.5/100 ventilator-days in neonates using the methods with 3 PDCA cycles over 20 months; Tripathi et al [5] reported a reduction in a pediatric ICU (PICU) from 3.55 to 2.59/100 intubation days after implementing a patient care policy targeting the risk factors, followed by extensive nursing and other personnel education over 12 months; Merkel et al [17] found a significant decrease in 3 years in the rate of UE in a neonatal intensive care unit (NICU) after bundles of potentially better practices had been implemented following sequential PDSA cycles; and Rachman and Mink [18] also reported that the effect of the quality improvement program to reduce UE had been successfully maintained even 9 years after implementation in the PICU.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This increase can be attributed to the hospital's having moved some experienced critical care nurses to support a newly set-up branch hospital, which decreased the quality of care in the ICU of our hospital's main branch ICU. Other studies [5,1618] report similar findings in different populations. Fontanez-Nieves et al [16] reported a significant reduction of UE from 16.1 to 4.5/100 ventilator-days in neonates using the methods with 3 PDCA cycles over 20 months; Tripathi et al [5] reported a reduction in a pediatric ICU (PICU) from 3.55 to 2.59/100 intubation days after implementing a patient care policy targeting the risk factors, followed by extensive nursing and other personnel education over 12 months; Merkel et al [17] found a significant decrease in 3 years in the rate of UE in a neonatal intensive care unit (NICU) after bundles of potentially better practices had been implemented following sequential PDSA cycles; and Rachman and Mink [18] also reported that the effect of the quality improvement program to reduce UE had been successfully maintained even 9 years after implementation in the PICU.…”
Section: Discussionsupporting
confidence: 72%
“…Fontanez-Nieves et al [16] reported a significant reduction of UE from 16.1 to 4.5/100 ventilator-days in neonates using the methods with 3 PDCA cycles over 20 months; Tripathi et al [5] reported a reduction in a pediatric ICU (PICU) from 3.55 to 2.59/100 intubation days after implementing a patient care policy targeting the risk factors, followed by extensive nursing and other personnel education over 12 months; Merkel et al [17] found a significant decrease in 3 years in the rate of UE in a neonatal intensive care unit (NICU) after bundles of potentially better practices had been implemented following sequential PDSA cycles; and Rachman and Mink [18] also reported that the effect of the quality improvement program to reduce UE had been successfully maintained even 9 years after implementation in the PICU. In summary, our findings and those of other studies [5,1618] indicate that a multidisciplinary quality improvement program can effectively reduce UE in the ICU, and the effect can be maintained and even improved 15 years after the sequential introduction of different interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5 One of the largest studies to evaluate UEs in newborns included 304 patients ventilated for a total of 3,786 days over 5.5 years. In this cohort, 115 UEs occurred in 59 patients, and the reintubation rate was 66%, 2 similar to the reintubation rate of 69% in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…4 Since the 1970s, studies have reported high rates of UE in NICUs. 58 In a large, multicenter study using a NICU-specific trigger tool, UEs were the fourth most common adverse event in the NICU and the most common event specifically associated with mechanical ventilation. 9 Although the incidence and consequences of UEs are well-known, the epidemiologic factors associated with UEs in critically ill newborns, especially infants at greatest risk of UE, are poorly described making prospective evidence- based interventions difficult to determine.…”
mentioning
confidence: 99%